Socialization of Bukittinggi City Government Innovations in Disciplining Professional Actors Through Tourism Hero Cards - Yuniardi, Indra; Rasyid, Anuar; Ismandianto, Ismandianto (Rumah Jurnal UNEJ, 2024)
Based on data from the Bukittinggi Tourism Office, the number of tourists continues to increase. The high number of visits does have a positive impact but the lack of control of professional actors creates problems for visitors. Congestion and cleanliness are one of the impacts of the lack of supervision of the traders. In response to this, the Bukittinggi City Government created an innovation to discipline professional groups through the Tourism Hero Card. The research is descriptive qualitative research. Data were collected through observation, interviews, and documentation. The results of the research show that the Hero Tourism Card is socialized directly and also informed through social media. The innovation has an impact on professional actors because it is quite effective in structuring traders and the location of the trading area. However, Covid-19 caused the innovation diffusion process at the beginning of its release to be less effective. The lack of access to information for some professional actors makes the Hero Tourism Card innovation need special attention in the future.